Optimalisasi Pengikatan Tanin Daun Nangka dengan Protein Bovine Serum Albumin (Optimalisation Binding of Jackfruit Leaves Tannin with Bovine Serum Albumin Protein) - Wahidin Teguh Sasongko; Lies Mira Yusiati; Zaenal Bachruddin; Mugiono (Mugiono) (Buletin Peternakan, 2010)
Tannins are high molecular weight polyphenol compounds with ability to bind proteins. Based on the structure,albumin are simple globular molecule protein. Optimalisation binding of jackfruit leave tannins to bovine serum (BSA)albumin was done in two stages. The first stage was to determine levels of tannins and condensed tannins in jackfruit leaves grown in mediterranean soil types. Second research was optimalisation binding of jackfruit leaf tannins withbovine serum albumin. In the second stage there was the determination of protein-percipitable phenolics compound and protein content using Lowry method. The data showed total phenol content was 10.63%, total tannin was 7.08%, andcondensed tannins 5.57%. The optimum capacity phenolic compound to bind protein of bovine serum albumin was 5.71+0.18 mg BSA/100 mg dry matter of jackfruit leaf, while 1 g tannin could bind 23.149 g BSA or 1 g condensedtannin could bind 28.885 g BSA.(Key words: Tannin, Total phenol, Total tannin, Condensed tannin, Bovine serum albumin)